NEW OPPORTUNITIES FOR IMMUNE THERAPY IN PATIENTS WITH DISSEMINATED RECURRENT SQUAMOUS CELL CARCINOMA OF THE HEAD AND NECK - A. M. Mudunov; M. N. Narimanov; D. A. Safarov (Опухоли головы и шеи)
Patients with head and neck squamous cell carcinoma diagnosed with recurrent tumor or distant metastases usually have the worst prognosis. Chemotherapeutic options are very limited in these patients; there is a probability of drug resistance development. The researchers continue to search more effective and less toxic drugs. In the current article, we analyze the results of the latest randomized clinical trials devoted the assessment of novel antitumor immunotherapeutic drugs – PD-1 inhibitors – in patients with head and neck squamous cell carcinoma. This studies reveal new possibilities for the treatment of these patients.